Financial analysis of ha tay pharmaceutical joint stock Company performance from year 2015 to year 2017 - Vu, Phuong Chi (2020)
The study focuses on researching, systematizing and contributing to clarify theoretical knowledge of analyzing financial activities in general and analyzing financial capability of enterprises in particular. The basic objective of the thesis is based on financial data of Ha Tay Pharmaceutical Joint Stock Company in 2015 - 2017 to calculate and identify indicators that reflect the enterprise’s actual financial capacity, to predict future financial capacity as well as to point out financial risks that business may face. In addition, the research would offer some solutions and recommendations to improve financial capacity and business performance of the company.